2018
DOI: 10.18805/ijar.b-3453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of egg yolk based and egg yolk free soya bean milk based extenders for cryopreservation of Zebu cattle and buffalo semen

Abstract: This study was undertaken on three mature bulls each of Gir cattle and Surti buffalo breeds to evaluate the comparative efficacy of egg yolk based standard TFYG (Tris-citrate-fructose-yolk-glycerol) extender and egg yolk free soybean based commercial extenders Optixcell® (IMV, France) and Andromed® (Minitube, Germany) under split-sample technique. The ejaculates (9/bull) were extended @ 100×10 6 sperm ml -1 with three extenders and frozen using biofreezer following 4 hr of equilibration. The pooled means of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The absence of significant differences between TEY and TSBL in all rabbit sperm parameters studied post dilution, equilibration, and thawing may be due to good quality of the composition of both semen extender according to Samad (1985) and Chaudhari and Mshelia (2002), who stated that semen extender must be contained sources of energy (glucose in both), buffering capacity (Tris in both), protectant against cold shock (egg yolk in TEY and SBL in TSBL), cryoprotectant (glycerol in both), and antibiotics (Lincomycin and streptomycin in both). The lecithin in soybean or lecithin and lipoprotein contents in egg yolk together contribute to the preservation of the lipoprotein sheath of the sperm cell (Kumar et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…The absence of significant differences between TEY and TSBL in all rabbit sperm parameters studied post dilution, equilibration, and thawing may be due to good quality of the composition of both semen extender according to Samad (1985) and Chaudhari and Mshelia (2002), who stated that semen extender must be contained sources of energy (glucose in both), buffering capacity (Tris in both), protectant against cold shock (egg yolk in TEY and SBL in TSBL), cryoprotectant (glycerol in both), and antibiotics (Lincomycin and streptomycin in both). The lecithin in soybean or lecithin and lipoprotein contents in egg yolk together contribute to the preservation of the lipoprotein sheath of the sperm cell (Kumar et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…The present findings in control TFYG extender during cryopreservation of semen concurred well with the previous reports of Dhami et al (1994Dhami et al ( , 1995 and Patel et al (2020) in cattle and buffalo semen cryopreserved with same extender. Chaudhary et al (2018) reported comparable high HOS reactive sperm on dilution (77-82%), but lower values in post-thaw semen (28% each) of both Gir and Surti buffalo semen. Zodinsanga et al (2015) observed 93 and 80% postthaw HOS reactive sperm in purebred and crossbred bulls, respectively.…”
Section: Effect On Sperm Motility Viability and Hos Reactivitymentioning
confidence: 86%